VATS-Video-Assisted Thoracic Surgery The Past, Present Status and Future - Dhaliwal, RS (Journal of Universal College of Medical Sciences, 2013)
Video assisted thoracic surgery (VATS) has developed very rapidly in the last over two decade and is very good alternative to conventional open thoracotomy as a standard procedure for simple thoracic operations and as an option or complementary procedure for some more complex operations. In this paper we will review its developmental history, the present status and future prospective. DOI: http://dx.doi.org/10.3126/jucms.v1i1.8424 Journal of Universal College of Medical Sciences Vol.1(1) 2013: 42-57